Curso-Taller - Berdichevsky Porteny, Fernando; Cutler, Christopher; Melul, Sara; Siri, Leonardo Nicola; Mireles, Marta; Carrasco Sosa, Salvador; San Miguel, José Luis; Mondragón Solis, Jesús Luis; Monroy, Hugo; Perez, Francisco (Revista Mexicana de Ingenieria Biomedica, 2018)
"Medición de parámetros fisiológicos por métodos no-invasivos" "Microprocesadores aplicados a la medicina"